2018
DOI: 10.1073/pnas.1712312115
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis mRNA decay landscape arises from specialized RNA decay substrates, decapping-mediated feedback, and redundancy

Abstract: The decay of mRNA plays a vital role in modulating mRNA abundance, which, in turn, influences cellular and organismal processes. In plants and metazoans, three distinct pathways carry out the decay of most cytoplasmic mRNAs: The mRNA decapping complex, which requires the scaffold protein VARICOSE (VCS), removes a protective 5' cap, allowing for 5' to 3' decay via EXORIBONUCLEASE4 (XRN4, XRN1 in metazoans and yeast), and both the exosome and SUPPRESSOR OF VCS (SOV)/DIS3L2 degrade RNAs in the 3' to 5' direction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(180 citation statements)
references
References 58 publications
(82 reference statements)
8
170
2
Order By: Relevance
“…Triplicate biological samples were sequenced to an average depth of 22.7 million reads. After data normalization and exclusion of low abundance mRNAs, transcript abundances were used to model decay rates for each gene and genotype 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Triplicate biological samples were sequenced to an average depth of 22.7 million reads. After data normalization and exclusion of low abundance mRNAs, transcript abundances were used to model decay rates for each gene and genotype 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Since all three RHs colocalize with DCP2 and VCS, we hypothesized that their substrates are degraded in a decapping-dependent manner. A parallel decay experiment was performed in the decapping mutant vcs-7 11 , and co-analysis of rh6812 and vcs-7 effects on decay identified 5,832 out of 6,941 RH substrates (84%) as VCS substrates (Fig. 4e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also found that RNA stability correlates with distinct biological 387 functions (Narsai et al, 2007, Sorenson et al, 2018. To test this, we performed a 388 gene classification analysis using MAPMAN on the five different clusters described 389 before (Thimm et al, 2004).…”
Section: Rna-seq Library Preparation (See Materials and Methods For Dementioning
confidence: 98%
“…Sequence motifs in the 3'UTR that control transcript degradation are known (Rabani et al, 2017), yet little information exists on how structure plays into this. A recent study on mRNA decay in Arabidopsis showed that transcripts with enriched A content and depleted G content in 5' UTRs exhibited faster decay rates (Sorenson et al 2018). Given that AU base-pairing is weaker than GC base-pairing, these results may implicate saltinduced 5' UTR unfolding (increased reactivity) as a mechanism that exposes transcripts to nucleolytic attack.…”
Section: Novel Concordancy Analysis Reveals Synergistic Roles Of Tranmentioning
confidence: 98%